2014
DOI: 10.1016/j.bbadis.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Vascular wall extracellular matrix proteins and vascular diseases

Abstract: Extracellular matrix proteins form the basic structure of blood vessels. Along with providing basic structural support to blood vessels, matrix proteins interact with different sets of vascular cells via cell surface integrin or non-integrin receptors. Such interactions induce vascular cell de novo synthesis of new matrix proteins during blood vessel development or remodeling. Under pathological conditions, vascular matrix proteins undergo proteolytic processing, yielding bioactive fragments to influence vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
248
0
21

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(274 citation statements)
references
References 187 publications
(198 reference statements)
5
248
0
21
Order By: Relevance
“…This chemical might represent a promising agent for the treatment of small-sized aneurysms. ECM proteins, especially collagen and elastin, form the basic structure of blood vessels and provide architectural scaffolds for vessels, which benefit from their resistance to biomechanical stress [31]. Collagen is a stiff protein that limits vessel distension, while elastin contributes to arterial elasticity.…”
Section: Resultsmentioning
confidence: 99%
“…This chemical might represent a promising agent for the treatment of small-sized aneurysms. ECM proteins, especially collagen and elastin, form the basic structure of blood vessels and provide architectural scaffolds for vessels, which benefit from their resistance to biomechanical stress [31]. Collagen is a stiff protein that limits vessel distension, while elastin contributes to arterial elasticity.…”
Section: Resultsmentioning
confidence: 99%
“…Proliferative arteritis in dogs presents microscopic similarities to early stages of atherosclerosis where there is intimal GAG deposition and smooth muscle proliferation (9). Although we were unable to perform immunohistochemistry in order to determine the origin of spindle cells other authors verified a smooth muscle immunophenotype in this cell population (3,4,6,10).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of vascular GAG undergo changes with aging or in vascular diseases such atherosclerosis and hypertension. The final consequence is the remodeling of the vessel wall (3,7,10). Proliferative arteritis in dogs presents microscopic similarities to early stages of atherosclerosis where there is intimal GAG deposition and smooth muscle proliferation (9).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that the adventitial layer contains progenitors that trans-differentiate into VSMCs (Sartore et al 2001;Hoofnagle et al 2004;Hu et al 2004;Passman et al 2008). The composition of the ECM secreted by vascular cell types, and by VSMCs in particular, varies depending on the type of blood vessel and in response to developmental, physiological, and pathological stimuli (Kelleher et al 2004;Xu and Shi 2014). For example, a study of the type of ECM components secreted by VSMCs at various stages of mouse development identified a critical period from embryonic day E14 to 2 weeks after birth during which expression of matrix proteins, such as elastin and fibrillar collagens, is very pronounced, and which is followed by a period of low-expression that continues into adulthood (Kelleher et al 2004;Wagenseil and Mecham 2009).…”
Section: Structure Of the Arterial Vessel Wallmentioning
confidence: 99%